2018
DOI: 10.1164/rccm.201707-1331oc
|View full text |Cite
|
Sign up to set email alerts
|

A Disintegrin and Metalloproteinase Domain-8: A Novel Protective Proteinase in Chronic Obstructive Pulmonary Disease

Abstract: Adam8 deficiency increases CS-induced lung inflammation, emphysema, and airway mucus cell metaplasia. Strategies that increase or prolong ADAM8's expression in the lung may have therapeutic efficacy in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 54 publications
1
28
0
Order By: Relevance
“…The balance of proteinases and anti-proteinases is a classic concept in the pathogenesis of COPD [90]. Two recent murine studies have demonstrated the potential role of a disintegrin and a metalloproteinase domain-8 (ADAM8) and ADAM9 in cigarette smoke induced COPD-like pathology [91, 92]. In one study, cigarette smoke exposed ADAM8 knockout mice had greater lung inflammation, airspace enlargement and small airway goblet cell metaplasia compared to cigarette smoke exposed wildtype mice.…”
Section: Histopathological Features Of Small Airway Disease In Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…The balance of proteinases and anti-proteinases is a classic concept in the pathogenesis of COPD [90]. Two recent murine studies have demonstrated the potential role of a disintegrin and a metalloproteinase domain-8 (ADAM8) and ADAM9 in cigarette smoke induced COPD-like pathology [91, 92]. In one study, cigarette smoke exposed ADAM8 knockout mice had greater lung inflammation, airspace enlargement and small airway goblet cell metaplasia compared to cigarette smoke exposed wildtype mice.…”
Section: Histopathological Features Of Small Airway Disease In Copdmentioning
confidence: 99%
“…Interestingly there was no difference in the extent of small airway fibrosis. ADAM8 expression was also reduced in COPD patients compared to controls [91]. In contrast, ADAM9 was shown to promote airspace enlargement, goblet cell metaplasia and fibrosis.…”
Section: Histopathological Features Of Small Airway Disease In Copdmentioning
confidence: 99%
“…Proteases and their regulators, such as AAT (alpha-1 antitrypsin), have garnered recent interest for their role in COPD pathogenesis. Polverino and colleagues reported that the expression of ADAM8 (ADAM metallopeptidase domain 8), a metalloproteinase, was higher in the airway epithelia of nonsmokers than in smokers without COPD and was further decreased in individuals with COPD (12). Similarly, cigarette smoke-exposed mice had decreased ADAM8 expression, and ADAM8 knockout mice developed more emphysema after cigarette smoke exposure than wild-type mice.…”
Section: Protease-antiprotease Balancementioning
confidence: 99%
“…Similarly, cigarette smoke-exposed mice had decreased ADAM8 expression, and ADAM8 knockout mice developed more emphysema after cigarette smoke exposure than wild-type mice. ADAM8 induced epidermal growth factor receptor shedding from airway epithelial cells, leading to decreased mucin gene expression (11,12). In contrast, Wang and colleagues reported higher ADAM9 expression in airway epithelia from patients with COPD than from nonsmokers and smokers without COPD (14).…”
Section: Protease-antiprotease Balancementioning
confidence: 99%
“…Most prior studies of proteinases in the pathogenesis of COPD have focused on the contributions of serine proteinases, matrix metalloproteinases (MMPs), and cysteine proteinases [ 4 ]. However, the family of ADAM proteinases (a d isintegrin a nd m etalloproteinase domain) are emerging as key contributors to COPD as two family members (ADAM8 and ADAM9) have been recently strongly linked to COPD [ 6 , 7 ]. ADAMs are multi-domain proteinases that are expressed on cell surfaces [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%